Pengaruh Clamping Frame Kayu Meranti dan ASTM A36 pada Friction Spot Joining AL 1100 dan PVC - Raharjo, Rudianto; Hamidi, Nurkholis; Widodo, Teguh Dwi; Bintarto, Redi; Habibulfalah, Endi (Rekayasa Mesin, 2020)
In this paper, the effect of welding parameters on the shear strength of Al-PVC hybrid structures was discussed. This Research developed welding parameters in the form of Plunge Depth, heating time, and clamping frame materials. By these different parameters would result in different shear strength of welded materials. Following optimization of the process, a detailed comparison of the properties and microstructures of two different materials (meranti wood and ASTM A36 Steel) would affect to different values of thermal conductivity. The Aluminum used was Al 1100, which was welded by using a friction stir spot welding method with Polyvinyl Chloride (PVC). In this study, by the different heating times, the shear test was carried out with the ASTM D3163 standard. In this study, it was found that the maximum temperature of Aluminum occurs during the 2nd second of the welding process and then decreased in the 5th second until 60th second. However, the optimum shear strength found at 20th second. Following heat transfer and degradation materials, the 2mm plunge depth has a higher temperature and higher shear strength than 1,5mm plunge depth. Differences in the response of the two depth were attributed to the difference in mechanical interlocking. This study found that the ASTM A36 clamping frame maximum shear load of 182.4 N is higher than meranti wood frame of 125.5 N. Differences in these value are attributed to the differences of the thermal conductivity, which meranti wood had a lower thermal conductivity than ASTM A36. These have findings significant implications for the commercial application of welding hybrid structures. The best way to take advantage of the benefit of AL-PVC Structure Hybrid for friction stir spot welding would appear to be 20 second heating time, 2mm plunge depth with ASTM clamping frame.